The Magnitude and Impact of Bullying among School Pupils in Muscat, Oman: A Cross-Sectional Study - Muna Al-Saadoon; Yahya M. Al-Farsi; Syed Rizvi; Marwan Al-Sharbati; Abdullah Al-Jabri; Sufyan Almamari; Wafaa Al-Baluki; Samir Al-Adawi (The Scientific World Journal)
Research about bullying among school pupils in the Arab/Muslim population is scarce. This study evaluates the characteristics of bullying and its impact among school pupils in Oman via cross-sectional survey among eighth grade school pupils (n = 1,229) during the academic year 2006-2007. The participants were selected using stratified random selection among 6 administrative divisions of one the governorates in the country. Data were collected using self-completed structured questionnaires. This study found similar percentages of males and females (76%) have experienced one form of bullying, and the majority of the incidents (80%) occurred in the vicinity of the school. In almost half of the cases, the bullying was initiated by a student of the same age or older than the victim. The most common type of bullying encountered in this study was verbal (47.7%), followed by misuse (45.9%), physical (43.9%), and, finally, social isolation/exclusion (22.5%). Although the failure of an academic year was uncommon among victims of bullying, the number of pupils who missed 4–6 and ≥7 school days was higher among bullied pupils. If this study will withstand further research, educational initiatives are needed to mitigate the rate of bullying in Oman.